2018
DOI: 10.1136/bcr-2018-225136
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rectus sheath haematoma due to cough on apixaban

Abstract: DesCripTionA 69-year-old woman on apixaban for 4 years due to her atrial fibrillation presented with severe left lower abdominal pain. She was discharged from the hospital 4 days prior after treatment for influenza and had finished a course of oseltamivir. She did not receive any heparin products and was continued on apixaban during that admission. A few hours before presentation, she reported coughing severely with sudden onset of excruciating abdominal pain. She denied trauma or injury to the abdomen. On exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…As the time of writing, only 6 case reports of DOAC-associated RSH, with three associated with apixaban and three associated with rivaroxaban. (5,(8)(9)(10)(11)(12) The majority of patients were female and all of them were older than 65 years of age. Drug interaction and reduced renal function may be contributing factors to the development of RSH in some of the cases (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…As the time of writing, only 6 case reports of DOAC-associated RSH, with three associated with apixaban and three associated with rivaroxaban. (5,(8)(9)(10)(11)(12) The majority of patients were female and all of them were older than 65 years of age. Drug interaction and reduced renal function may be contributing factors to the development of RSH in some of the cases (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…On rare occasions, it can also occur spontaneously (Kapan et al, 2008;Athanasios et al, 2014;McCarthy & Bellam, 2010;Patel et al, 2016). Among all of the factors mentioned above, direct blunt abdominal trauma and the use of anticoagulants are the most commonly reported risk factors (Alla et al, 2010;Elango et al, 2018;Donaldson et al, 2007;Cherry & Mueller, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Gunasekaran et al, reported a case of spontaneous rectus sheath hematoma in a 68-year-old female taking apixaban for a provoked VTE after a recent knee replacement surgery. She required two units of packed red blood cell transfusion and an IVC filter placement as anticoagulation was discontinued [39,40]. Aktas et al, reported a case of spontaneous rectus sheath hematoma in a 71-year-old female with atrial fibrillation taking apixaban [41].…”
Section: Epidemiologymentioning
confidence: 99%
“…Immediate discontinuation of the offending medication is essential for all patients, but the consequence of discontinuation of such agents due to thromboembolic events needs to be considered [78]. The half-lives of these DOACs are short; hence, there could be thrombotic events when withholding the agents even for a short period [40]. Therefore, in minimal bleeding, it may not be required to hold the anticoagulant at all.…”
Section: Treatmentmentioning
confidence: 99%